Milicevic3306
asked
in Electronic Devices
Mar 28, 2018
recategorized
Nov 15, 2020
by soujanyareddy13

44 views
0 votes

Consider the constant current source shown in the figure below. Let $\beta$ represent the current gain of the transistor.

The load current $I_0$ through $R_L$ is

- $I_0 = \bigg( \frac{\beta+1}{\beta} \bigg) \frac{V_{ref}}{R}$
- $I_0 = \bigg(\frac{\beta}{\beta+1}\bigg) \frac{V_{ref}}{R}$
- $I_0=\bigg (\frac{\beta+1}{\beta} \bigg ) \frac{V_{ref}}{2R}$
- $I_0 = \bigg (\frac{\beta}{\beta+1} \bigg) \frac{V_{ref}}{2R}$